2022
DOI: 10.3390/cancers14071636
|View full text |Cite
|
Sign up to set email alerts
|

Intention to Inform Relatives, Rates of Cascade Testing, and Preference for Patient-Mediated Communication in Families Concerned with Hereditary Breast and Ovarian Cancer and Lynch Syndrome: The Swiss CASCADE Cohort

Abstract: Cascade screening for Tier 1 cancer genetic conditions is a significant public health intervention because it identifies untested relatives of individuals known to carry pathogenic variants associated with hereditary breast and ovarian cancer (HBOC) and Lynch syndrome (LS). The Swiss CASCADE is a family-based, open-ended cohort, including carriers of HBOC- and LS-associated pathogenic variants and their relatives. This paper describes rates of cascade screening in relatives from HBOC- and LS- harboring familie… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 39 publications
1
6
0
Order By: Relevance
“…However, our own data, and data from an independent Swiss-based sample [ 38 ], suggest that although probands embrace some forms of provider-mediated communication, they do not want to be excluded from this process. Survey data collected as part of the CASCADE study indicate that only one in three or fewer individuals with HBOC- or LS-associated pathogenic variants endorsed provider-mediated communication [ 31 ]. Other studies have also shown a preference for proband-mediated family communication [ 11 , 22 , 39 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, our own data, and data from an independent Swiss-based sample [ 38 ], suggest that although probands embrace some forms of provider-mediated communication, they do not want to be excluded from this process. Survey data collected as part of the CASCADE study indicate that only one in three or fewer individuals with HBOC- or LS-associated pathogenic variants endorsed provider-mediated communication [ 31 ]. Other studies have also shown a preference for proband-mediated family communication [ 11 , 22 , 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…This descriptive, grounded theory-based analysis used individual interviews and focus groups to collect narrative data from a sample of women identified as carriers of HBOC-associated pathogenic variants. Individuals were recruited from the CASCADE study, an open-ended cohort designed to elicit factors that enhance cascade genetic screening for HBOC and Lynch syndrome in Switzerland (NCT03124212) [ 31 ]. Confirmed carriers of pathogenic variants who were 18 years or older were recruited from university centers, cantonal hospitals, and private praxis in three linguistic regions of Switzerland.…”
Section: Methodsmentioning
confidence: 99%
“…Basic health insurance in Switzerland does not cover the cost of cascade testing for SDR and TDR [ 56 ]. Given that approximately half of the non-invited relatives in the CASCADE cohort are SDR and TDR [ 35 ], out-of-pocket costs (about CHF 400 or USD 410) could be a barrier for the approximately 27% of untested SDR and TDR in the study. Additional reasons for foregoing testing, such as not interested, busy, and valuing other life events more than genetic testing, have been reported also by others [ 16 , 21 , 27 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Excluded are individuals diagnosed with variants of unknown significance, non-blood relatives, and critically ill patients unable to provide written consent. Details about the cohort have been previously published [ 35 ]. For this analysis, we focused on comparing relatives who did not have genetic testing (GT (−) group) with those who had testing (GT (+) group).…”
Section: Methodsmentioning
confidence: 99%
“…The cohort was initiated in Switzerland, which had acquired most data at the time of the workshop. The development of the Swiss CASCADE and rates of genetic testing among relatives have been presented ( Sarki et al, 2022a ; Sarki et al, 2022b ). In short, the Swiss CASCADE had consented 365 index cases (276 HBOC and 89 LS) and 158 relatives (140 HBOC and 18 LS).…”
Section: Methodsmentioning
confidence: 99%